PENGARUH PEMELIHARAAN MESIN DAN KETERAMPILAN TERHADAP PRODUKTIVITAS WATER TREATMENT PLANT SOFTENER PT. NUTRIFOOD INDONESIA - Arda Falah Eriatama; Wiwik Rachmarwi (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2023)
The purpose of this study was to determine the effect of maintenance and skills on the productivity of the WTP at PT. Indonesian Nutrifood. The method used is a quantitative method. The data collection method in this study was through questionnaires. Data analysis techniques in this analysis are classical assumption tests, regression, multiple linear, coefficient of determination and hypothesis testing. The results of this study indicate that the maintenance and skill variables have a positive and significant effect on the productivity of the PAPs. Based on the t test showing that maintenance and skills have a positive effect on the productivity of the WTP, it is concluded that the hypothesis is accepted